(untitled) (Research, Society and Development, 2022)
Introduction: Onion (Allium cepa) is a widely used ingredient in Brazilian gastronomy, as well as being used medicinally for over 4000 thousand years as a treatment for a variety of diseases, including headaches, insect bites, intestinal worms and tumors. Objective: to elucidate the main evidence about the possible anticarcinogenic potential conferred on onions. Methodology: this is a descriptive research of the type narrative review of the literature, which sought to answer the main evidence about the anticarcinogenic potential of onion. The research was carried out through online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases. Information Services. Results and Discussion: Onion intake may decrease the risk of sarcoma and carcinoma in various tissues and organs such as stomach, colon, esophagus, prostate, bladder, liver, lungs, breasts, skin and brain. Thus, it is possible to affirm that onion exerts its anticarcinogenic action indirectly through different mechanisms: alteration of carcinogenic metabolism or increasing the activity of detoxification enzyme systems that increases carcinogenic polarity, inhibition of oxidative damage due to its antioxidant action; inhibition of cell proliferation by inducing apoptosis and inhibition of cell division, prevention of chromosomal damage (anticlastogenic effect); and inhibition of lipoxygenase and cyclooxygenase activities (anti-inflammatory effect). Final Thoughts: While the minimum daily intake needed to reduce cancer risk is yet to be determined, onion intake may offer protection against cancer development.